The romantic national tale and the question of Ireland - Ferris, Ina (Cambridge studies in Romanticism, 2002)
Ferris examines the way in which the problem of 'incomplete union'generated by the formation of the United Kingdom in 1800 destabilised British public discourse in the early decades of the nineteenth century, and the emergence of the national tale as the main genre to address these issues.